PENGARUH ROTASI KANTOR AKUNTAN PUBLIK DAN PENGENDALIAN INTERNAL TERHADAP FEE AUDIT DI INDONESIA DAN MALAYSIA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia dan Bursa Malaysia Tahun 2017-2019) - Ninda Argita Oksaviani; Herry Laksito (Diponegoro Journal of Accounting, 2021)
The aim of this study is to examine the effects of audit firm rotation and internal control on audit fees in Indonesia and Malaysia. The independent variables that used in this study are audit firm rotation and internal control, while the dependent variable is audit fees. This study also used firm size, ROA, leverage, growth of revenue, loss for the year, and audit firm size as control variables. The population in this study consists of all manufacturing companies in Indonesia Stock Exchange (IDX) and Kuala Lumpur Stock Exchange (KLSE) for the period 2017-2019. Total sample of this study are 108 companies in IDX and 123 companies in KLSE. Hypotheses testing in this study uses multiple regression analysis. Statistical technique used in this study is panel data. The result of this study indicate that audit firm rotation and internal control have a significant effect on audit fees in Indonesia and Malaysia. Welch-Satterthwaite test indicates that there is difference of audit firm rotation on audit fees between Indonesia and Malaysia and there is no differences of internal control on audit fees between Indonesia and Malaysia.